2020
DOI: 10.1177/0957650920915306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volute tongue angle on the performance and flow unsteadiness of an automotive electronic cooling pump

Abstract: Automotive electronic cooling pump is the core component of the new energy vehicle cooling system, with the exclusive advantages of high efficiency and low vibration which will bring a broad market prospect. However, the rotor–volute interaction between impeller blades and volute tongue is a severe problem which can result in the performance degradation and unsteady flow fields of pumps. The influences of volute tongue angle on hydraulic performance and fluid stability are investigated in this study. The flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Chan et al compared two different design techniques that are conventionally used in the design of volutes for centrifugal pumps and found that the imbalanced forces due to the geometry of the volute need to be taken into consideration, especially in centrifugal pumps [7]. Zhang, Alemi, and Lu et al discussed the influence of the shape, position, and setting angle of the volute tongue on hydraulic performance and pressure pulsation of a centrifugal pump [10][11][12]. Allali and Tan et al discovered that different shapes of volute cross-sections (circular, rectangular, and trapezoidal) had different effects on flow velocity and pressure variation in volutes [13,14].…”
Section: Alemi Et Al Conducted Research On Two Volute Design Methods ...mentioning
confidence: 99%
“…Chan et al compared two different design techniques that are conventionally used in the design of volutes for centrifugal pumps and found that the imbalanced forces due to the geometry of the volute need to be taken into consideration, especially in centrifugal pumps [7]. Zhang, Alemi, and Lu et al discussed the influence of the shape, position, and setting angle of the volute tongue on hydraulic performance and pressure pulsation of a centrifugal pump [10][11][12]. Allali and Tan et al discovered that different shapes of volute cross-sections (circular, rectangular, and trapezoidal) had different effects on flow velocity and pressure variation in volutes [13,14].…”
Section: Alemi Et Al Conducted Research On Two Volute Design Methods ...mentioning
confidence: 99%
“…Similarly, electronic components in safety systems can detect potential hazards, warning the driver and even taking control of the vehicle, preventing accidents. Additionally, electronic components in electric and hybrid vehicles are essential for the efficient operation of the electric drivetrain, providing improved range, better acceleration, and reduced emissions [23][24][25][26].…”
Section: Advantagesmentioning
confidence: 99%
“…A visualization method of flow loss based on the entropy generation theory was proposed. The transfer equation of entropy for incompressible fluid can be described as [25]:…”
Section: Entropy Generation Theorymentioning
confidence: 99%